ESENSI DAN PEMETAAN TEORETISASI MEDIA KOMUNIKASI DALAM PERSPEKTIF KARL MARX - Rustono Farady Marta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Perspective of Karl Marx lies in the viewpoint of the "economy", because the essence of the theory and its development include macro and micro scope as patterns of thought in economics. Marx as one of the most influential intellectuals of the time. Marx's theory has a direct impact upon closing of age on March 17, 1883 in London. Marx offers basic prepositions in the process theoryzing as normative ideological implications that has, among others through the social class differences were criticized on the conditions of exploitation of the proletariat by the bourgeoisie with the mental control of production in society and create a false consciousness among the proletariat. Marx believed that the mass media are owned by the public suprastuktur and media communications content is dominated by social class. Keywords: Media Communication Theorizing, Karl Marx Perspective